Modeling a reconfigurable legged robot with movable center of body using multi-body dynamics approaches - Nur Salasus Salwa, Khairul Anuar; Addie Irawan, Hashim; Zulkifli, Mansor; Mohammad Fadhil, Abas; Nor Maniha, Abdul Ghani (IEEE Xplore, 2025)
This paper presents the modeling and simulation of a reconfigurable hexapod robot, Hexaquad, featuring a movable center of body (MCB) mechanism using MATLAB Simscape Multibody. The study applies a multibody dynamics (MBD) approach with spatial contact force modeling to enhance stability and terrain adaptability. The MCB mechanism improves weight distribution, reduces body oscillations, and significantly enhances CoG stability during motion. Kinematic modeling based on the Coxa Coordinate System (CCS), joint initialization, and contact force configuration are detailed. Stand-up motion tests under different initial leg configurations show that flatter leg postures yield better spatial and angular stability. Results indicate a CoG deviation reduction of up to 4.7%, reflecting a 35-50% improvement in dynamic stability. The study offers a practical simulation framework for developing real-time control strategies for legged robots.